Epidemiological investigation of recurrent outbreaks of duck plague in selected Haor (wetland) areas of Bangladesh - Khan, Kamrul Ahmed; Saha, Sukumar; Hossain, Muhammed Tofazzal; Haque, Md. Enamul; Haq, Mohammad Mansorol; Islam, Mohammad Alimul (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: A cross sectional study was conducted in five Haor (wetland) districts of Bangladesh to investigate the epidemiological parameters and associated factors of recurrent outbreak of duck plague (DP) on the basis of molecular detection. Materials and methods: A total of 450 randomly selected duck farms containing 175,467 ducks were investigated for their morbidity, mortality and case fatality rates from December 2012 to November 2014. The farms were surveyed and the owners were interviewed using a prepared questionnaire about husbandry practice, disease history, bio-security measures, and flock and farmer details. A total of 150 samples (liver=50, intestine=50 and oro-pharyngeal tissue=50) were collected from duck plague suspected sick/dead ducks of north eastern part of Bangladesh during outbreak season. Samples were processed and PCR was done directly from the samples using primers specific for duck plague virus. Results: Out of 150 test samples of the fifty duck plague suspected ducks of fifty outbreaks, 90 samples (60%) of 36 ducks of thirty six outbreaks (72%) were found positive by PCR. Overall prevalence of duck plague was 8% at farm level and 3.30% at flock level. Morbidity, mortality and case fatality rates of duck plague at farm level were 52.08, 29.62 and 56.86%, respectively. Of the 22 variables selected for this study, 16 were found significant and the remaining 6 were found non-significant statistically. Conclusion: Results of the epidemiological investigation of the present study regarding duck mortality suggesting that education and training of the farmers on bio-security, modern husbandry practice, regular vaccination and innovation of cost effective intensive duck farming methods are necessary to control recurrent duck plague outbreak in Haor (wetland) areas. http://doi.org/10.5455/javar.2018.e256